2010
DOI: 10.1016/j.fertnstert.2010.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Local injury of the endometrium induces an inflammatory response that promotes successful implantation

Abstract: Objective-To study whether an injury-induced inflammation might be the mechanism underlying the favorable effect of endometrial biopsy on the implantation rate in in vitro fertilization (IVF) patients. Design-Controlled clinical study.Setting-A medical center IVF unit and a research institute. Patient(s)-Women undergoing IVF who had previous failed treatment cycles.Intervention(s)-Endometrial samples were collected from two groups of patients on day 21 of their spontaneous menstrual cycle. The experimental, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
270
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(288 citation statements)
references
References 33 publications
8
270
0
10
Order By: Relevance
“…However, those reports varied in terms of the characteristics of the device that was used for injury, the degree of injury, and the timing of the intervention. Various devices have been used to injure the endometrium, such as hysteroscopes and biopsy catheters 1, 3, 4, 5, 6, 7, 9. In this study, an endometrial sampler was used that was considered to be an appropriate tool for inducing a mild endometrial injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those reports varied in terms of the characteristics of the device that was used for injury, the degree of injury, and the timing of the intervention. Various devices have been used to injure the endometrium, such as hysteroscopes and biopsy catheters 1, 3, 4, 5, 6, 7, 9. In this study, an endometrial sampler was used that was considered to be an appropriate tool for inducing a mild endometrial injury.…”
Section: Discussionmentioning
confidence: 99%
“…One possible cause for this is poor endometrial receptivity. Various approaches to addressing this problem have been explored and some recent studies have shown that local endometrial injury can improve both the implantation rates and pregnancy outcomes in patients with unexplained recurrent implantation failure 1, 2, 3, 4, 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Studies in infertile women with repeated implantation failure (RIF) have demonstrated improvement in PR after a mechanical injury caused by EB (Potdar et al, 2012). It is reported that causing mechanical trauma to the endometrium in the cycle before ET (Barash et al, 2003, Karimzadeh et al, 2009 or during the ongoing cycle (Boomsma et al, 2009a, Gnainsky et al, 2010, Huang et al, 2011, actually improves endometrial receptivity and pregnancy success. A systematic review, (Potdar et al, 2012) reported the pregnancy outcomes of seven controlled studies (n=2062) in women with RIF.…”
Section: Discussionmentioning
confidence: 99%
“…Some controversy exists about the effect of collecting endometrial samples on subsequent reproductive performance. In subfertile women, local endometrial injuries in the cycle before ET improved the pregnancy rates (Barash et al, 2003, Gnainsky et al, 2010. In cattle, some studies suggest that these procedures impair uterine function (Zaayer andVan der Horst, 1986, Etherington et al, 1988) whilst others report satisfactory pregnancy rates but without making a comparison with control non-sampled group (Rhoads et al, 2008, Chapwanya et al, 2010.…”
Section: Systematic Review Of the Effect Of Different Methods Of Utermentioning
confidence: 99%
See 1 more Smart Citation